Modelling and Numerics for Respiratory Aerosols. (14th September 2015) - Boudin, Laurent; Grandmont, Céline; Lorz, Alexander; Moussa, Ayman
Abstract: In this work, we present a model for an aerosol (air/particle mixture) in the respiratory system. It consists of the incompressible Navier-Stokes equations for the air and the Vlasov equation for the particles in a fixed or moving domain, coupled through a drag force. We propose a discretization of the model, investigate stability properties of the numerical code and sensitivity to parameter perturbation. We also focus on the influence of the aerosol on the airflow.